Cost accounting to determine prices: How well do prices reflect costs in the German DRG-system? - Schreyögg, Jonas; Tiemann, Oliver; Busse, Reinhard (Health care management science, 2006)
Germany has recently introduced a system of Diagnosis Related Groups (DRGs) to engender more appropriate resource allocation. The following article describes the German DRG-system and the methodologies used to determine prices. It analyses the extent to which prices, or calculated cost weights, reflect the actual costs incurred by hospitals for their respective services. We reveal that a "compression" of DRG cost weights occurs, and that the data sample used to calculate cost weights is lacking in terms of its representativeness. Although cost data accuracy has improved over the last few years there are still a number of challenges that need to be addressed.